Estimation of the radiation dose for pediatric CBCT indications: a prospective study on ProMax3D. Issue 3 (22nd January 2018) - Marcu, Maria; Hedesiu, Mihaela; Salmon, Benjamin; Pauwels, Ruben; Stratis, Andreas; Oenning, Anne Caroline Costa; Cohen, Mike E.; Jacobs, Reinhilde; Baciut, Mihaela; Roman, Raluca; Dinu, Cristian; Rotaru, Horatiu; et al.
Abstract : Background: An increasing number of CBCT units and a wide variability of radiation doses have been reported in dentistry lately. Aim: To estimate the effective, cumulative, and organ absorbed doses in children exposed to CBCT over 2 years. Design: A prospective study was conducted in children who underwent CBCT diagnostic imaging with the ProMax3D machine. Organ and effective doses were calculated by Monte Carlo simulation using 5‐ and 8‐year‐old pediatric voxel phantoms. Extrapolation procedures were applied to estimate doses for other ages and CBCT protocols used in clinical conditions. Results: The median effective dose was 137.9 μSv, and the median cumulative dose was 231.4 μSv. Statistically significant differences in the effective doses and cumulative doses were found for various indications of CBCT in children ( P < 0.001). The median absorbed organ dose for brain and thyroid was significantly higher for the clinical condition that required large FOVs (2.5 mGy and 1.05 mGy, respectively) compared to medium (0.19 and 0.51 mGy) and small FOVs (0.07 and 0.24 mGy; P < 0.05). The radiation dose of salivary glands did not vary significantly with FOV. Conclusion: The results revealed the variation of CBCT doses and the influence of FOV size in pediatric exposure.